Metabolic dysfunction related to typical and atypical antipsychotics in drug-naive patients with nonaffective psychosis: a prospective comparative study. Issue 3 (July 2017) - Asaad, Tarek; Meguid, Marwa A.; El Missiry, Marwa; Ali, Rami; Bassim, Rasha E.; Taha, Sameh
Abstract : Background: Metabolic syndrome induced by antipsychotic (AP) drugs is commonly encountered in patients with nonaffective psychosis. Epidemiological studies report that 52% of patients with severe mental illness such as schizophrenia, schizoaffective disorder, bipolar disorder, and depression have metabolic syndrome compared with only 23–25% of the general population and thus have a markedly decreased life expectancy. Aim: The study aimed to compare the effect of typical and atypical APs on different metabolic parameters in newly diagnosed drug-naive patients with psychotic disorders for a period of 12 weeks, which were divided into three follow-up visits, and clarify the associated risk factors. Patients and methods: A convenient sample of 80 patients 18–50 years of age, of both sexes, from both inpatient and outpatient departments of the Institute of Psychiatry were screened for possible inclusion in the study. All patients were interviewed using SCID-I. Patients fulfilling the DSM-IV diagnostic criteria for schizophrenia, delusional disorder, brief psychotic disorder, and/or schizophreniform disorder, who had never been treated with psychotropic medication, and who had no comorbid medical conditions were included. Using computerized randomization, patients were assigned to two groups: group I received typical APs and group II received atypical APs. Demographic and clinical data were collected and anthropometric measurements were taken. Finally, laboratory analysis was performed for assessment of fasting blood glucose and lipid profile. Results: The mean age of the patients was 26.03±6.53 years in group I and 28.48±6.29 years in group II. Group I patients were prescribed haloperidol, trifluoperazine, and flupenthixol, whereas group II patients were prescribed risperidone, olanzapine, and quetiapine. With regard to weight gain, patients in both groups were found to gain weight; however, it was more evident in patients given atypical APs, with a statistically significant difference across visits. Fasting blood glucose level increased significantly across visits in each group, but a comparison between the two groups did not show statistical significance. With regard to lipid profiles, cholesterol levels increased across visits and showed a statistically significant difference in visit 3; serum triglycerides and low-density lipoprotein increased as well but with no statistical significance; high-density lipoprotein decreased across visits but with no statistical significance. Conclusion: AP medications, although providing a tremendous change in the lives of patients and giving them a better future, have imposed more of a burden on their metabolic profiles. This is especially true of atypical compounds.